Preserved micturition after intradetrusor onabotulinumtoxinA injection for treatment of neurogenic bladder dysfunction in Parkinson's disease. Issue 1 (December 2016) - Knüpfer, Stephanie; Schneider, Susanne; Averhoff, Mareike; Naumann, Carsten; Deuschl, Günther; Jünemann, Klaus-Peter; Hamann, Moritz
Abstract Background To assess the efficacy and safety of intradetrusor onabotulinumtoxinA (OnabotA) injection treatment in patients with neurogenic lower urinary tract dysfunction (NLUTD), especially for patients with Parkinson disease (PD). Methods PD patients refractory to oral antimuscarinic participated in an off-label use study and were evaluated prior and after 200 IU OnabotA injection into detrusor muscle, including trigone. Changes due to treatment were evaluated using bladder diaries, urodynamics, and questionnaires. Statistical analysis comprised Wilcoxon rank-sum test. Values are presented as mean ± standard deviation. Results Ten PD patients (4 female and 6 male, mean age: 67.9 ± 5.36 years) with LUTD were enrolled. All patients tolerated the treatment. Bladder diary variables decreased significantly (p  ≤ 0.011 ) after OnabotA injection compared to variables prior injection. Desire to void and maximum bladder capacity increased significantly in urodynamics (p  ≤ 0.05 ). Maximum detrusor pressure during voiding phase normalised from 56.2 to 18.75 cm/H2 0. Detrusor overactivity was less often detectable. All patients voided spontaneously. Mean post void residual (PVR) volume was 77.0 ± 119.78 mL postoperatively. No urinary retention or side effects have been observed during/after treatment. Mean follow-up time was 4 months (range of 1–12). 4 patients requested repeated injection after a mean period of 10 months between first and second injection. Conclusions Our data confirm the efficacy and safety of 200 IU OnabotA injection in patients with neurogenic LUTD due to PD. The risk of urinary retention or high post-urinary residual volumes seems to be minor after OnabotA-injection. More research is needed with larger sample size to confirm the significance of these findings. Trial registration Trial Number:ISRCTN 11857462, Registration Date 2016/10/08